Matrix-GLA-Protein and Vascular Calcification: Can Diet Influence the Consequences of Matrix GLA Protein Inactivation? A Review - Masoud, Mirzaie; Kusnirova, Josefina; Addicks, Johann Philipp; Fatehpur, Sheila (International Journal of Innovative Research in Medical Science, 2021)
In vascular calcification, as a physiological process, intimal arterial calcification (IAC) associated with increased cardiovascular risk is distinguished from medial arterial calcification (MAC) localized mainly in the lamina elatica interna, which are not only based on different pathophysiological mechanisms. They also lead to different cardiovascular diseases. While intimal arterial calcification involves inflammation and lipid accumulation, a calcification process similar to desmal ossification plays the main role in medial arterial calcification. In this context, the phenotype change of smooth muscle cells from muscular type to synthesizing form in the tunica media is considered to be of great importance, which puts the matrix GLA protein, mainly involved in bone metabolism, in the center of interest. The present review work elucidates the molecular biological basis of interaction of matrix GLA protein subunits in the pathogenesis of vascular calcifications and the influence of diet on the consequences of underactivation of matrix GLA protein.